Gestión Administrativa en el Registro de la Propiedad de la Ciudad de Babahoyo - Mejía Yulán, Betty Juliana (2020)
The administration serves to provide different solutions to organizational problems through an effective and efficient combination of human, material, financial and technological resources, with the objective of determining the causes that are generating problems in the administrative management of the city property registry. Babahoyo, the descriptive method was used and as an information gathering technique, an interview was carried out with the collaborators and a survey was carried out with external clients, for the subsequent analysis of the processes and procedures in the different sections of the department that generated problems, from the space Limited physical to carry out the activities, the registry system whose software has fulfilled its useful life and the absence of a computer program (Excel) that accelerates the development of procedures, the implementation of new tactics and systems will make work faster. and the performance improves and the divisi n areas allow a correct sequence order and control tasks.